2019
DOI: 10.1111/myc.13026
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic identification of three new species in Alternaria section Infectoriae causing human cutaneous infection

Abstract: Summary Background Cutaneous phaeohyphomycosis is an emerging disease in immunocompromised patients, being Alternaria one of the most common genera reported as a causative agent. Species identification is not carried out mainly due to the complexity of the genus. Analysis of the ITS barcode has become standard for fungal identification, but in Alternaria it is only able to discriminate among species‐groups or sections. Methods We present three cases of cutaneous infection caused by Alternaria isolates morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…As a result, we reviewed 228 published reports. We identified and included 149 reports on 201 cases of dematiaceous fungal infections in SOT recipients 21–169 . The majority (134/149; 90%) of included reports scored ≥ 2 of three possible points on our bias assessment (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, we reviewed 228 published reports. We identified and included 149 reports on 201 cases of dematiaceous fungal infections in SOT recipients 21–169 . The majority (134/149; 90%) of included reports scored ≥ 2 of three possible points on our bias assessment (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…However, such analyses also revealed the high genetic variability of this section compared to others [59]. Using the combined datasets of ITS rDNA, gpd, rpb2, tef1 and ATPase, new species have recently been defined within the section Infectoriae [51,55]. Using similar loci and comparisons with all of the species for which the corresponding sequences were available in databank, we showed that several isolates included in this section clustered independently with little to no statistical support for their phylogenetic position, which is similar to previous observations [54].…”
Section: Discussionmentioning
confidence: 96%
“…Alternaria species from section Infectoriae were detected as common species in food, the indoor environment and human cutaneous infections [23,51,[60][61][62]. Recent studies have reported the incidence of species belonging to this section on potato plants in the Pacific North-west [58], in Pakistan [63], in Iran [17], in Russia [64], and our inoculation assays have indeed confirmed that the species from this section could be pathogenic to this host as well as to tomatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a worldwide distribution with diverse lifestyles, including saprobes, pathogens of plants and humans, endophytes, epiphytes and hyperparasites ( Ramesh 2003 ; Kirk et al 2008 ; Zhang et al 2012 ; Hyde et al 2013 ; Sun et al 2019 ; Ferdinandez et al 2021 ). Many species in Alternaria Nee s , Curvularia Boedijn and Corynespora Güssow, can invade medicinal plants and cause leaf spots and other diseases, as economically important plant pathogens ( Mathiyazhagan et al 2004 ; Abtahi and Nourani 2017 ; Zhang et al 2020 ), and some also pose a threat to human health ( Hyde et al 2018 ; Iturrieta-González et al 2020 ). Endophytes in Pleosporales also show important biocontrol value ( Su et al 2014 ; De Silva et al 2019; Hyde et al 2019 ), for example, an extract from Cochliobolus spicifer R.R.…”
Section: Introductionmentioning
confidence: 99%